Menelusuri Pemahaman Patriarki Dalam Tafsir Q.S. An-Nisa:34 dan Impikasinya Terhadap Tren Penurunan Pernikahan di Indonesia - Gustianda, Nana (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study explores the understanding of patriarchy in the interpretation of Q.S. An-Nisa:34 and examines its implications for the declining marriage trend in Indonesia. The interpretation of Q.S. An-Nisa:34 is often seen as supporting patriarchal values, which significantly impact social structures and gender perceptions. With social changes, Indonesia has experienced a decline in marriage trends, which may be influenced by more egalitarian religious interpretations. This study aims to understand how the verse is interpreted in society and how this understanding contributes to the declining marriage trend This research uses a qualitative approach with the maudhu'i method and a little touch of hermeneutics. It interprets Q.S an-Nisa':34 by putting forward the views of the mufassir. The findings show that the interpretation of Q.S. An-Nisa:34 is understood as a basis in the household where men are qawwam (leaders or protectors). This means that there is a big task that men must do, namely providing for their wives and children. If the task of earning a living is not done, then the nature of leadership is lost. The misunderstanding of Q.S. An-Nisa:34 contributes to the changing perception of marriage, which in turn affects marriage trends in Indonesia.